Phytoremediation of PAHs in Contaminated Soils: A Review (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2021)
Polycyclic aromatic hydrocarbons (PAHs), which are also part of persistent organic pollutants (POPs), are considered to be especially toxic to humans (carcinogenic), likewise to plants, microorganisms and other living organisms. PAHs soil contamination occurs by storage leaking, transport loss, the land disposal of petroleum waste, and accidental or intentional spills. Due to their ubiquitous occurrence, recalcitrance, bioaccumulation potential and carcinogenic activity, PAHs are a significant environmental concern. The methods of controlling and repairing PAH-contaminated soils mainly include physical remediation, chemical remediation and phytoremediation. However, there was an increasing focus on phytoremediation technologies as a result of their unique advantages, including low cost, lack of secondary pollution and large-area application. Phytoremediation is therefore one of the soil remediation technologies with the greatest potential.
Keywords: Bioremediation; Phytoremediation; PAHs; Soil; Pollution